Dietary Protein Source and Litter Condition Alter Broiler Chicken Intestinal Macrophage and Mitotically Active Cell Populations - Keel, A. Jacob; Calderon, Allan J.; Tejeda, Oscar J.; Starkey, Jessica D.; Starkey, Charles W. (Frontiers in Veterinary Science, 2022)
As antibiotic-free (ABF) broiler production continues to increase, understanding the development and local immune response in the intestines of ABF broilers is essential. Mitotically active cells, the majority of which will become enterocytes, help maintain the intestinal epithelial barrier. Macrophages prevent pathogen invasion by their phagocytic activity, functioning as immune response amplifying cells to aid in the recruitment of additional immune cells, and stimulating cytokine production in other adjacent cells. The objective of this experiment was to evaluate commonly used practical production practices on intestinal cell mitotic activity and local intestinal immunological responses. A randomized complete block design experiment with a 3 × 2 factorial treatment structure was conducted. The 3 dietary protein sources were: soybean meal (SBM), a mix of 50% poultry by-product meal and 50% feather meal (PFM), and porcine meat and bone meal (MBM) and broilers were reared on either new litter (NL) or used litter (UL). On d 3, 8, 11, 15, and 21, 6 birds per treatment from 6 blocks (total n = 36 per d) were randomly selected for sampling. Broilers were injected intraperitoneally with 5’-bromo-2’-deoxyuridine (BrdU) 1 h prior to sampling to label mitotically active cells. Samples were analyzed using cryohistology and immunofluorescence to determine the density of mitotically active cells and macrophages. Mitotically active cell and macrophage densities changed in both the duodenum and ileum over time. Neither dietary protein source nor litter condition affected mitotically active cell or macrophage densities in the duodenum on d 11 and 21 or in the ileum on d 3, 8, 11, and 15. However, on d 3 and 15 in the duodenum (P ≤ 0.0126) and d 21 in the ileum (P ≤ 0.0009), broilers reared on UL had greater mitotically active cell densities than those reared on NL. On d 8 in the duodenum, broilers fed MBM had increased macrophage density compared with those fed PFM and SBM (P ≤ 0.0401). These results indicate dietary protein source and litter condition may impact the physiology of the broiler small intestine, though additional work with this model is necessary to understand the underlying mechanisms.